2017
DOI: 10.1007/s00399-017-0543-x
|View full text |Cite|
|
Sign up to set email alerts
|

Atrial thrombogenesis in atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common cause of thromboembolic complications. The risk of suffering a thromboembolic complication depends on the accompanying cardiac risk factors and the patient's age. For patients who have an increased risk, which is now classified using the CHA2DS2-VASc score, initiation of long-term oral anticoagulation is the first-line treatment. In AF, thrombi arise in the left atrial appendage. The present review will summarize the basic pathophysiology of thrombogenesis in AF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Studies have demonstrated endocardial changes in atrial tissue specimens. Prothrombogenic factors (vWF, adhesion molecules VCAM-1, P-selectin, MCP-1) are expressed at the surface of endothelial cells causing platelets and leucocytes to adhere to the atrial endocardium in particular in the left atrial appendage [83,193,209], which causes the initiation of thrombus formation [209,210]. Diseases or conditions such as diabetes mellitus, heart failure, and ageing (CHA2DS2VASc Parameters) are known to increase alterations by oxidative stress pathways within endothelial cells, and thereby further increase the expression of prothrombogenic molecules.…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated endocardial changes in atrial tissue specimens. Prothrombogenic factors (vWF, adhesion molecules VCAM-1, P-selectin, MCP-1) are expressed at the surface of endothelial cells causing platelets and leucocytes to adhere to the atrial endocardium in particular in the left atrial appendage [83,193,209], which causes the initiation of thrombus formation [209,210]. Diseases or conditions such as diabetes mellitus, heart failure, and ageing (CHA2DS2VASc Parameters) are known to increase alterations by oxidative stress pathways within endothelial cells, and thereby further increase the expression of prothrombogenic molecules.…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…Recently, post hoc studies from large randomized controlled trials suggested that the burden of AF (Figure 3) as well as the type of AF (paroxysmal versus persistent/permanent AF) might be a factor, which drives differences in patient outcome [213][214][215][216][217]. Such clinical differences might be explained at least to some extent by differences in atrial cardiomyopathies and ventricular oxidative stress levels during various types of AF [210]. The recent hypothesis is that the burden of AF contributes to differences in the occurrence of specific clinical events such as cognitive decline, stroke, or myocardial infarction.…”
Section: Atrial Endocardial Remodeling As a Cause Of Thrombogenesis And Strokementioning
confidence: 99%
“…Sex-gender differences were reported in arterial structure, alterations in blood flow, shear stress and endothelial function [62]. Furthermore, an influence of sex has been described in atrial structure and function, which could affect atrial thrombogenesis mechanisms [63][64][65]. Also, gender-related alterations in inflammatory and pro-coagulant markers, thrombogenic particles and platelet aggregation may play a role [62].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The last review of this series addresses the problem of thrombogenesis in AF as a major contributor to the high risk of stroke in this disease [19]. The authors recapitulate our current understanding of the coagulation cascade and explain the modern concept of "prothrombotic endocardial remodelling".…”
Section: Novel Clinical and Experimental Aspects Of Atrial Fibrillationmentioning
confidence: 99%